Use of proteolysis in gerodietetic products - Peshuk, Ludmila; Galenko, Oleg (My University, 2014)
Analysis of experimental data and also their mathematical treatment, allowed to justify the use of enzyme preparation - nutritive collagenase to increase functional groups in the by-products of II category (rumen of cattle).
Keywords: геродієтичні продукти; геронтологія; протеоліз; геродиетичекские продукты; геронтология; протеолиз; gerodietetic products; proteolysis; gerontology; кафедра технології м’яса і м’ясних продуктів